SOJIWAN TEMPLE AND PLAOSAN TEMPLE: SOME GEOMETRICAL FEATURES - Mahmudah, Faisa Nirbita (Ethnomathematics Journal, 2024)
Cultural objects around learners can become real contexts for building awareness of and studying mathematics. The present study is aimed at exploring and identifying ethnomathematical values which are contained in the building structures and reliefs of Sojiwan Temple and Plaosan Temple, specifically in the materials of geometry and measurements. The study is descriptive qualitative research. Data sources were observations, interviews, documentations, and literary study. Results show that the two temples have a similarity in that they contain four concept domains in the materials of geometry and measurements that can be studied through ethnomathematics; namely the materials of characteristics, circumferences and areas of flat shapes, volumes and areas of space shapes (flat sides and curve), congruency and similarity that can be integrated in the temple structure buildings, and geometric transformations that can be integrated in the reliefs on the temples. Ethnomathematics learning based on these two temples can be used to help learners' achievement of understanding of the material concepts and cultivation of characters.